Peran Zakat dalam Stabilitas Ekonomi Syariah - Refi Herdian fauzi A; Akbar Pratama Aditya B; Rido maulana C (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Zakat is one of the pillars of Islam. Therefore, zakat is an obligation for Muslims. And in the Islamic economic system, zakat is an important factor in improving people's welfare in the economic field. However, the idea arises that the economic system in Muslim society, in this case zakat, is considered incompatible with modern life because it can slow down the pace of the economy. The research method used is library research which is based on qualitative descriptive data. So a comprehensive explanation is needed regarding zakat in the Islamic economic system which has an important role in improving the Islamic economy in society.